Fixed Point Theorems for Generalized θ-ϕ-Contractions in G-Metric Spaces - Dingwei Zheng (Journal of Function Spaces)
We introduce the notion of generalized θ-ϕ contraction and establish some new fixed point theorems for this contraction in the setting of complete G-metric spaces. The results presented in the paper improve, extend, and unify some known results. Finally, we give an example to illustrate them.